In patients undergoing Fontan completion, does a younger age at operation result in better long-term exercise capacity and prognosis?. (31st July 2018) - Daley, Michael; d'Udekem, Yves
Abstract: A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was 'In [patients undergoing Fontan completion], does [a younger age at operation] result in [better long-term exercise capacity and prognosis]?'. Altogether, 304 papers were found using the reported search, of which 10 represented the best evidence to answer the clinical question. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results of these papers are tabulated. Of these, 2 recent large reviews describe a better or a non-significant trend towards better outcomes when the Fontan procedure is performed at a younger age. This is supported by 4 studies demonstrating better long-term exercise capacity when patients undergo Fontan completion at a younger age. Additionally, 2 other studies describe increased rates of failure, adverse events and arrhythmias with older age at Fontan completion. Two publications describe non-inferior outcomes in patients with an older age at Fontan completion, although limited by the number of patients and follow-up. We conclude that the Fontan operation should be performed at an early age (<7 years) because the data show higher survival and fewer adverse events, and the gradual decline in exercise capacity in Fontan patients appears accelerated when the Fontan operation is performed at older age.